"Auditoría administrativa y su incidencia en los procesos operacionales de la empresa cooperativa de ahorro y crédito 29 de octubre Ltda., cantón Quevedo, año 2013 - Alvarado Rosero, Gema Rocío (2015)
Cooperative Savings and Credit Company October 29 Ltda., Is located in Canton Quevedo, October 7th street between the thirteenth and fourteenth. The Management Audit is an important contribution to the company, because of the significance of standards and policies induced therein, is to observe a control of operational processes in order to study the result in this way, determine how it affects its liquidity. When you run this investigation arises as General Purpose. To determine the incidence of administrative audit on the operational processes of the company Cooperativa de Ahorro y Credito Ltda October 29, Quevedo Canton 2013. The research work has been prepared by methods undeniably they contributed the steps for its creation which were: Fuentes, COSO II Method, flowcharts, narratives, Creating auditing firm, descriptive and explanatory research, no experimental design, population and sample, budget and the analysis and interpretation of the results.The methods used in the research were: Investigative, scientific, inductive and empirical; The techniques were: observation and interview; The types were; descriptive, exploratory, analytical, causal and literature. The research will be published their findings with recommendations set out in the Internal Control Report, also within the same will be released about the real financial situation of the company in that period. We evaluated each of the components of internal control was obtained resulting in a 37% confidence level, while the level of risk is 63%, considered as moderate, because the company is establishing some measure of control over processes operational. The use of internal control tools it possible to obtain reliable information on the areas of decision making by management. The Internal Control findings allowed to determine among the poor control of the results of services and products offered, the lack of contingency plans to deal with risk. The internal control report, allowed to display the results, evaluation and conclusions of the Internal Control to the operational processes of the company "Cooperativa October 29". Keywords: Audit, Management Audit, Operational Processes.